CRITICAL DISCOURSE ANALYSIS ON KOMPAS DAILY NEWSPAPER REPORT ON PROFITEERING THROUGH THE NAMES OF PRESIDENT JOKOWI AND VICE PRESIDENT JUSUF KALLA - Marianus Fergilus Lede Todo; I Wayan Budiarta (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
The objectives of this study were to (1) describe the structure of Kompas daily news texts about the profiteering of the names of Indonesian President Joko Widodo and Vice President Jusuf Kalla, (2) to explain the mental consciousness of journalists forming daily Kompas texts about profiteering the names of Indonesian President Joko Widodo and Vice President Jusuf Kalla, and (3) to explain the social context influencing the formation of Kompas daily texts about the profiteering of President Joko Widodo and Vice President Jusuf Kalla. The method used in this research was qualitative research method. The data used in this research was news texts from Kompas daily newspaper, which reported about the case of profiteering of the name of Indonesian President and Vice President. Data collection method employed was literature study. The data in was analyzed with the orientation of analytic descriptive method. The results of data analysis showed that at the level of macro structure, superstructure, and micro structure, the global meaning of discourse developed in the news is about the settlement of cases of profiteering of the President and Vice President. The act of profiteering on the name of Indonesian President and Vice President was judged only to delegitimize the authority of the President and Vice President and state institutions. Meanwhile, the journalist's mental awareness that formed the Kompas daily news texts includes role schemes and event schemes. While the social context that influenced the formation of the discourse of naming consists of power and access. The ideology reflected in Kompas daily news texts is Pancasila.